Turn off the faucet: Solving excess water consumption with individual meters - Paul E. Carrillo; Ivette Contreras; Carlos G. Scartascini (Inter-American Development Bank (IDB), 2021)
When consumption of water and other utilities is measured collectively and payment for such services is equally shared among members of the group, individuals may use more than what is socially optimal. In this paper, we evaluate how installation of individual meters affects water consumption. Using rich administrative data from the public water utility company in Quito, Ecuador, it is estimated that water consumption decreases by about 8% as a result of the introduction of individual metering. The effect is large and economically significant: in order to obtain the same effect prices would have to double. Individual water metering could be a useful tool to curve down consumption in both developing and developed countries.
Keywords: D12; D62; Q21; Q25; Q58; 330; Water consumption; Commons problem; Institutions; Individual meters; Price elasticity; Regression discontinuity; Difference-in-difference